EKSPLORASI ETNOMATEMATIKA PADA MAKANAN TRADISIONAL LAPET DAN ALAT MUSIK TAGANING - Lidya Kyrena Kharisma Pakpahan; Greises Hernasa Sidauruk; Rolas Alex Nababan; Amelia Siska Roma ito Nainggolan; Tia Steffani Rejeki Panjaitan; Icha Pranata Hutabarat; Diva Marlina Situngkir (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to explore the mathematical concepts embedded in local culture through an ethnomathematics approach applied to Lapet, a traditional food, and Taganing, a traditional musical instrument, as a source of contextual mathematics learning and as an effort to preserve cultural heritage. Both cultural objects were analyzed to identify mathematical elements such as plane figures, solid geometry, patterns and repetition, ratio and measurement, as well as time and temperature calculation. The method used was qualitative research with an ethnographic approach, employing literature study and direct observation of the Lapet-making process and the Taganing performance. The findings revealed that Lapet and Taganing embody various mathematical concepts related to geometry, patterns, measurement, and proportion. These findings indicate that both cultural artifacts represent the application of mathematical concepts in community life and have the potential to serve as contextual learning resources in ethnomathematics-based mathematics education. This study offers novelty by revealing the concept of time and temperature calculation in a traditional culinary process as an ethnomathematics element that has rarely been explored in similar studies, as well as by linking two distinct Batak cultural objects, namely traditional food and a traditional musical instrument, within a single integrated ethnomathematics study. These findings prove that local cultural heritage can serve as a contextual learning resource that enriches students' mathematical understanding while supporting the preservation of Batak culture in the field of education. ABSTRAK Penelitian ini bertujuan untuk mengeksplorasi konsep-konsep matematika yang terkandung dalam budaya lokal melalui pendekatan etnomatematika terhadap makanan tradisional Lapet dan alat musik tradisional Taganing sebagai sumber pembelajaran kontekstual matematika sekaligus upaya pelestarian budaya. Kedua objek budaya tersebut dianalisis untuk mengidentifikasi unsur-unsur matematika seperti bangun datar, bangun ruang, pola dan pengulangan, perbandingan dan pengukuran, hingga perhitungan waktu dan suhu. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan etnografi melalui studi literatur dan observasi langsung pada proses pembuatan Lapet serta pertunjukan musik Taganing. Hasil penelitian menunjukkan bahwa Lapet dan Taganing mengandung berbagai konsep matematika yang berkaitan dengan geometri, pola, pengukuran, dan perbandingan. Temuan ini menunjukkan bahwa kedua objek budaya tersebut merepresentasikan penerapan konsep matematika dalam kehidupan masyarakat serta berpotensi dimanfaatkan sebagai sumber pembelajaran matematika berbasis etnomatematika. Temuan ini membuktikan bahwa warisan budaya lokal dapat menjadi sumber pembelajaran kontekstual yang memperkaya pemahaman matematika siswa sekaligus mendukung pelestarian budaya Batak dalam dunia pendidikan.